Status of Waqf Properties As Debt’s Collateral - intan avi; Notaricia Sartika F.S.P.N; Made Ayu Trisnawati (Notaire, 2019)
The lack of understanding on land waqf creates many issues related to waqf itself, i.e. offers endowed land as deb’ts collateral. In Article 40 alphabeth (a) Law Number 41 Year 2004 on Waqf, there is prohibition to include waqf properties as collateral. Waqf properties’ status change that inchorent with Law Number 41 Year 2004 on Waqf, one of it is including land waqf as debt’s collateral will cause unwanted consequence on the collateral agreement itself. In fact, there are still violations on Article 40 alphabeth (a) Law Number 41 Year 2004 on Waqf. These situations are caused by minimum awareness on management of waqf properties from nadzir, heirs and bank as the creditor towards implementation of waqf properties’ status change. Therefore, consequence of waqf properties’ status change that violates Article 40 alphabeth (a) Law Number 41 Year 2004 on Waqf will not immediately null and void; however, debt’s repayment still needs to be fulfilled by debtor corresponds with Article 1131 BW. It required efforts to minimize issues on waqf through socialization of waqf towards nadzir, heirs, bank as creditor and wide community, especially waqf properties’ status change so there will not be any issues on implementation and management of waqf properties in the future.